A new species of Prohatschekia Nunes-Ruivo, 1954 (Siphonostomatoida: Hatschekiidae) from the scorpaenid fish, Scorpaena neglecta Temminck & Schlegel, 1843 (Scorpaeniformes: Scorpaenidae), in Korean waters - Moon, Seong Yong; Youn, Seok-Hyun; Maran, Balu Alagar Venmathi (Zootaxa, 2016)
A new species of parasitic copepod, Prohatschekia pseudocremouxi sp. nov. is described based on adult females collected from the gills of the scorpaenid fish, Scorpaena neglecta Temminck & Schlegel, 1843 caught in Korean waters. The new species is most closely related to P. cremouxi Nunes-Ruivo, 1954, but differs from it by the following combination of characters in the adult female: the size of the trunk which is about 3.7 times as long as cephalothorax; the short and strongly curved antennary claw; and the distal segment of the maxilla is tipped with a simple seta. This discovery raises the number of nominal species in Prohatschekia Nunes-Ruivo, 1954 to eight and represents the first record of the genus in Korea.